Efecto de la aplicación de dos fuentes nutricionales, y tres densidades de siembra en el cultivo de brócoli (Brassica oleracea var itálica) en la parroquia San Lorenzo, cantón Guaranda, provincia Bolívar - Lalangui Castillo, Stalin Santiago (2024)
The broccoli worldwide is growing in the cultivated area and the demand for market niches are increasingly demanding is in quality and food safety. In Ecuador due to the favorable climate conditions, it is cultivated especially for export by private companies, however, producers due to ignorance of valid technological alternatives, productivity indicators are low. This research was carried out in Amapolas, Guaranda canton, Bolívar province. The objectives were to terminate the effect of three planting densities with four nutritional sources and to perform the economic analysis of the Benefit-Cost Ratio (RB/C). The main factor A was three planting densities and factor B or subplots four nutritional sources and one control. There were 15 treatments with three repetitions, the Design of Complete Blocks was applied at random in split plot. Morphological and agronomic variables were evaluated. Analysis of variance, Tukey's 5% test, correlation, linear regression and economic analysis of RB/C were performed. Different effects of the main factors and interactions on agronomic variables and particularly yield was completed. The planting density of 0.30 m between plants and chemical fertilization were more efficient with the highest average yields, which were related to the highest net benefit. The components that increased yield were the upper averages of plant height, stem and head diameters, number of leaves per plant, corymbs per head, solids and head size. The best technological option was the T11: A3B1 treatment (0.30 m between plants and 300 kg/ha of 18-46-00) with 56320 kg/ha and an RB/C of 1.44. Finally, this study contributed to selecting valid technological alternatives to improve the diversity and sustainability of local production systems.